The Unburdening Effects of Forgiveness: Effects on Slant Perception and Jumping Height. (May 2015) - Zheng, Xue; Fehr, Ryan; Tai, Kenneth; Narayanan, Jayanth; Gelfand, Michele J.
Research shows that in the aftermath of conflict, forgiveness improves victims' well-being and the victim–offender relationship. Building on the research on embodied perception and economy of action, we demonstrate that forgiveness also has implications for victims' perceptions and behavior in the physical domain. Metaphorically, unforgiveness is a burden that can be lightened by forgiveness; we show that people induced to feel forgiveness perceive hills to be less steep (Study 1) and jump higher in an ostensible fitness test (Study 2) than people who are induced to feel unforgiveness. These findings suggest that forgiveness may lighten the physical burden of unforgiveness, providing evidence that forgiveness can help victims overcome the negative effects of conflict.